Students' Critical Thinking Process in Solving Contextual Problems Reviewed from Sensing and Intuition Learning Styles - rendy; Rooselyna Ekawati (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Critical thinking is a cognitive activity involving the ability to understand, analyze, evaluate, conclude, explain, and regulate thoughts systematically and objectively. This qualitative case study aims to describe students' critical thinking processes in solving contextual problems, specifically examining sensing and intuition learning styles. The research involved two 10th-grade students, one with a sensing style and one with an intuition style, selected via purposive sampling. Data collection utilized learning style questionnaires, math ability tests, contextual problem-solving tasks, and interviews. Data analysis was based on Mason et al. (2010) problem-solving stage indicators. The study found that the critical thinking processes of students with sensing and intuition learning styles are similar across the entry, attack, and review stages. In the entry stage, students gather important information, relate it to existing knowledge, and determine initial problem-solving steps. In the attack stage, they design a problem-solving strategy and execute it. In the review stage, students review solution steps, reflect on difficult parts, and explore alternative solutions.